I love you, Blue - Barroux 1965- (Otter-Barry Books, 2022)
When Jonas the lighthouse-keeper is rescued from the stormy sea by a whale, they become friends. But soon Blue the whale is in great danger too, and now he needs help from Jonas... This touching love story from world-renowned picture book creator, Barroux, beautifully highlights the urgency of saving our whales and our oceans.